Wolność sumienia i religii w art. 53 Konstytucji Rzeczypospolitej z dnia 2 kwietnia 1997 r. - Sobczyk, Paweł (Prawo Kanoniczne, 2001)
The 53rd article of the Constitution of the Republic of the Poland concerning the freedom of faith and religion, adopted of the 2nd of April 1997, is a result of a long lasting constitutional debate since 1989. Debate’s counterpatrs were: the President of the Polish Republic, the Constitutional Commission of the National Assembly, the Constitutional Commissions of the two chambers of Polish Parliament: the Sejm and the Senate, political Parties and citizens’ movements as well as individual persons. This broad engagement shows the importance of issues affecting freedoms and human rights of the citizens in the Republic of Poland. It underlines especially the idea of the constitutional legislator thet the freedom of faith and religion is a primary and indispensable right of a human beeing. More then that, as far as this freedom touches the crucial element of the human nature, it creates in every person a deep foundation for the existense of other freedoms.